2018
DOI: 10.1021/acscatal.8b01794
|View full text |Cite
|
Sign up to set email alerts
|

Boron- and Nitrogen-Codoped Molybdenum Carbide Nanoparticles Imbedded in a BCN Network as a Bifunctional Electrocatalyst for Hydrogen and Oxygen Evolution Reactions

Abstract: Boron-and nitrogen-codoped molybdenum carbide nanoparticles imbedded in a B,N-doped carbon network (B,N:Mo 2 C@BCN) have been synthesized as a noble-metal-free hybrid electrocatalyst via an eco-friendly organometallic complex of Mo imidazole and boric acid. When it is used as a bifunctional electrocatalyst for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in an aqueous alkaline solution, the B,N:Mo 2 C/BCN catalyst displays high activity and stability in basic electrolytes, better t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 43 publications
(76 reference statements)
2
76
0
Order By: Relevance
“…For this reason, we put primary focus on these non‐noble‐metal‐based electrocatalysts in this review. To overcome the high overpotential of the OER, numerous non‐noble‐metal‐based electrocatalysts have been developed, including metals/alloys,23,24 oxides,25–31 hydroxides,32–37 chalcogenides,38–42 phosphides,5,43,44 phosphates/borates,19,45,46 borides,47 nitrites,48,49 and other compounds 50,51…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we put primary focus on these non‐noble‐metal‐based electrocatalysts in this review. To overcome the high overpotential of the OER, numerous non‐noble‐metal‐based electrocatalysts have been developed, including metals/alloys,23,24 oxides,25–31 hydroxides,32–37 chalcogenides,38–42 phosphides,5,43,44 phosphates/borates,19,45,46 borides,47 nitrites,48,49 and other compounds 50,51…”
Section: Introductionmentioning
confidence: 99%
“…Developing non‐noble metal hydrogen evolution reaction (HER) catalysts aids the development of clean and sustainable energy sources to address the emerging energy and environmental crisis. [ 1 ] Among the large variety of non‐noble metal catalysts for HER that have been developed, including transition metal sulfides, [ 2 ] metal carbides, [ 3 ] metal nitrides, [ 4 ] metal phosphide, [ 5 ] and metal boride, [ 6 ] molybdenum disulfide (MoS 2 ) possesses great potential for HER. [ 7 ] The electronic structure of MoS 2 , and thus their catalytic efficiency, is highly sensitive to doping and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…The Mo x C/Ni heterostructures contributes to the formation of in situ NiOOH/NiO(OH) 2 and molybdenum species during the anodic process, increasing the active sites exposed on the composites and promoting the OER performance. The N-and P-dual doped carbon matrices also modify the composites electronic properties improving the charge transfer, facilitating chemisorption of the OHspecies, and stabilizing the Mo x C structures [22]. The mechanism of stabilization of Mo x C/Ni(OH) 2 nanoparticles in the Ni/Mo x C/rGOCS composite may be due to the higher surface area of the graphene carbon matrix, which allows a better introduction of N and P centers in the graphene structure and increases the internal degree of defects and disorder of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…In situ electro-oxidation studies during the OER have shown that Mo 2 C-based catalysts are converted to Mo oxides which have been demonstrated to be active for OER [20,21]. Furthermore, the presence of heteroatoms, such as B and N, could increase its activity and stability upon in situ oxidation of Mo 2 C [22]. Notably, coupling transition metal species with N-doped carbon-based materials is one of the most popular strategies for tailoring active and durable advanced composite electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%